SECOND INDOCHINA WAR - Ang, Cheng Guan. Link ([S.l.])
1 online resource.
Keywords: Drawing upon Vietnamese, Chinese, former Soviet, and American sources, Ang Cheng Guan provides an updated and concise account of the Vietnam War (1954-1975) from the Vietnamese communists' perspective.In the last few decades, discourse on the Second Indochina War has shifted towards the South and its allies. To mark the 50th anniversary of the fall of Saigon, Ang revisits the experiences of the North. Focusing on scholarship published within the last 30 years, the book reexamines the 1954 Geneva Conference, the end of the First Vietnam War through the Second Vietnam War to the 1975 Fall of Saigon, bringing readers up to date on the current state of the field.This book is a valuable resource for scholars and students of history, war studies, peace and conflict studies, as well as for those interested in the historical and contemporary implications of the Vietnam War.